2007
DOI: 10.1074/jbc.m610488200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p68 RNA Helicase Plays a Role in Platelet-derived Growth Factor-induced Cell Proliferation by Up-regulating Cyclin D1 and c-Myc Expression

Abstract: p68 RNA helicase is a protypical member of DEAD box family RNA helicase. The protein plays an important role in the cell developmental program and organ maturation. We demonstrated previously that, in response to growth factor platelet-derived growth factor (PDGF)-BB stimulation, p68 is phosphorylated at Tyr(593), and the phosphorylation of p68 promotes epithelial-mesenchymal transition via promoting beta-catenin nuclear translocation (Yang, L., Lin, C., and Liu, Z. R. (2006) Cell 127, 139-155). We show here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 71 publications
4
89
1
Order By: Relevance
“…LCN2 can enhance tumor growth and metastasis by protecting matrix metalloproteinase-9 from degradation and by increasing angiogenesis and/ or by promoting the epithelial to mesenchymal transition, which is associated with breast cancer progression (Leng et al, 2009;Yang et al, 2009). Therefore, this study identified a novel gene regulatory pathway (NFAT5 stimulation of S100A4 and LCN2 genes) that is coactivated by ddx5/ddx17 and that, together with previously reported ddx5 and ddx17 target genes like cyclin D1 and Snail (Shin et al, 2007;Yang et al, 2007;Carter et al, 2010), strengthens the role of ddx5 and ddx17 in tumor progression.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…LCN2 can enhance tumor growth and metastasis by protecting matrix metalloproteinase-9 from degradation and by increasing angiogenesis and/ or by promoting the epithelial to mesenchymal transition, which is associated with breast cancer progression (Leng et al, 2009;Yang et al, 2009). Therefore, this study identified a novel gene regulatory pathway (NFAT5 stimulation of S100A4 and LCN2 genes) that is coactivated by ddx5/ddx17 and that, together with previously reported ddx5 and ddx17 target genes like cyclin D1 and Snail (Shin et al, 2007;Yang et al, 2007;Carter et al, 2010), strengthens the role of ddx5 and ddx17 in tumor progression.…”
Section: Discussionsupporting
confidence: 66%
“…One intriguing possibility is that, depending on the cellular context, ddx5/ddx17-splicing activity or their transcriptional activity could dominate each other and this could participate in the dual function of ddx5 and ddx17 in cancer. In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005).…”
Section: Ip Flagmentioning
confidence: 99%
“…For example, human DDX5 has been shown to be overexpressed at the protein level in colorectal tumors as well as in the hepatic tumor cell lines, HT-29 and HCT116, which have undergone an epithelial-mesenchymal transition (Yang et al, 2005(Yang et al, , 2006. In addition, DDX5 has been shown to upregulate the expression of cyclin D1 along with c-myc genes, which promoted cell proliferation in a series of mammalian cell lines (Yang et al, 2007). Along these lines, the activity of oncoprotein EWS-FLI1 has been shown to be enhanced by RNA helicase H in the Ewing's sarcoma family of tumors (Toretsky et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we previously demonstrated that platelet-derived growth factor (PDGF) or EGF stimulation led to tyrosine phosphorylation of p68 RNA helicase in SW480 cells (16,19). Presently, our experiments demonstrated that binding to tyrosine phosphoprotein converted PKM2 from tetramer to dimer and therefore activated the protein kinase activity.…”
Section: Resultsmentioning
confidence: 63%